Correction to: Cost Effectiveness of Endovascular Ultrasound Renal Denervation in Patients with Resistant Hypertension (PharmacoEconomics - Open, (2024), 10.1007/s41669-024-00472-z) - Taylor, Rod S.; Bentley, Anthony; Metcalfe, Kaylie; Lobo, Melvin D.; Kirtane, Ajay J.; Azizi, Michel; Clark, Christopher; Murphy, Kieran; Boer, Jennifer H.; van Keep, Marjolijn; Ta, An Thu; Barman, Neil C.; et al. (PharmacoEconomics - Open, 2024)
In this article, the columns of Tables 2 and 3 have been incorrectly labelled: 'uRDN' and 'uRDN plus SoC'. They should read: ‘uRDN plus SoC’ and 'SoC alone’. The original article has been corrected.
CRIS-Team Scopus Importer:2024-05-17